Tuning the electronic communication of the Ru–O bond in ultrafine Ru nanoparticles to boost the alkaline electrocatalytic hydrogen production activity at large current density. Issue 16 (4th July 2022) - Feng, Weihang; Feng, Yongqiang; He, Yingrui; Chen, Junsheng; Wang, Hai; Luo, Tianmi; Hu, Yuzhu; Yuan, Chengke; Cao, Liyun; Feng, Liangliang; Huang, Jianfeng
Abstract : Ru nanoparticles coordinated with O supported on a carbon matrix were synthesized. The electron communication between Ru and O accelerated the charge transfer and thus improved the electrocatalytic hydrogen production activity. Abstract : The rational design and synthesis of efficient electrocatalysts for the hydrogen evolution reaction (HER) are of great importance for alkaline hydrogen production. This study describes a nanocomposite material design, in which ultrafine and small (2.0–3.5 nm) Ru nanoparticles coordinated with O atom sites are supported on a carbon matrix formed by C60 (OH) n (Ru–O/C-600). The Ru–O bonds create a channel of electron communication to facilitate charge transfer and improve the conductivity of electrocatalysts. The ultrafine and evenly-distributed Ru nanoparticles provide a high density of active sites to extend electrochemical surface areas. Ru–O/C-600 achieved a low overpotential of 32 mV at a current density of 10 mA cm −2 with a small Tafel slope of 51.8 mV dec −1 and long-term stability of 50 h. Moreover, Ru–O/C-600 also gave an output of 500 and 1000 mA cm −2 with an overpotential of 242 and 383 mV for practical use. These findings open up new avenues for developing Ru-based hybridization materials with enhanced electron transfer and abundant active sites for HER performance.